The Impact of Parenting and Cognitive Styles on Student Creativity: A Meta-Analytic - Endang Retnaningsih; Sumaryoto; Widodo (Postgraduate, University of Mataram, 2025)
Creativity is a crucial skill for success in the 21st century, yet the psychological and social factors that shape it remain only partially understood. This study seeks to explore the influence of parenting patterns and cognitive styles on student creativity through a systematic and quantitative meta-analysis. A total of 24 empirical studies published between 2017 and 2025 were examined using JASP software with a random-effects model. Data were sourced from online databases including ScienceDirect, Google Scholar, SINTA, and the Garuda Portal by applying the keywords Parenting, Cognitive Style, and Creativity. Only quantitative studies that reported adequate statistical details—such as Fisher or ANOVA (F), Student’s t-test (t), correlation coefficient (r), and sample size (N)—were included. The analysis showed that democratic parenting (r = 0.30, p < 0.001) and a field-independent cognitive style (r = 0.63, p < 0.01) have a significant and strong positive association with student creativity. These results emphasize the role of moderating factors like grade level, classroom environment, and school context in fostering creative abilities. The study contributes valuable insights and offers evidence-based recommendations for educational policies and practices aimed at enhancing creativity through family engagement and cognitive development strategies.